Carrier-envelope offset frequency measurement by means of an external optical resonator - Giannotti, Dario; Suerra, Edoardo; Canella, Francesco; Cialdi, Simone; Laporta, Paolo; Galzerano, Gianluca (Frontiers in Physics, 2023)
A general-purpose method based on the implementation of asymmetric Pound-Drever-Hall (PDH) technique is proposed to measure the Carrier-Envelope Offset (CEO) frequency of a mode-locked laser by using an external optical cavity. By analyzing the synchronously demodulated signal of the spectrally filtered cavity reflection when the optical resonator is locked to the mode-locked laser, a discriminating signal that depends on the relative frequency offset between the mode-locked and optical cavity comb-like spectra is obtained. For a given geometry and a group delay dispersion (GDD) of the cavity parameters (i.e., a known cavity modes' offset), this signal can be used to retrieve the laser CEO. This approach turns out to be advantageous in terms of setup complexity with respect to other well-known techniques, that rely on non-linear frequency generation, such as f-2f interferometers. In addition, this method can be used to precisely determine the laser-cavity spectral coupling, which is an important topic in cavity enhanced spectroscopy and non-linear optics applications. After the theoretical description of the generalized asymmetric PDH signal, an experimental validation of the proposed method is reported using an Er-doped fiber frequency comb source at 1550 nm and with 250 MHz repetition rate, locked to a linear optical cavity with 1 GHz free-spectral-range. The theoretical effect of the GDD is confirmed experimentally by using a different cavity configuration. Moreover, the comparison with the CEO frequency values measured with an f-2f interferometer demonstrates the feasibility of the proposed method.